COMMUNICATION PRIVACY RESTRICTIONS DURING THE COVID-19 PANDEMIC - Anzhelika N. Izotova (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The work is devoted to the issues of restricting the privacy of communication which is an integral part of privacy, a necessary condition for freedom of speech and for trust in communication services, and is crucial for the development of the information society. In the context of the pandemic, it became possible to restrict the confidentiality of communication in the context of geolocating people through their mobile devices based on data from mobile operators. Therefore, it is important to note the essential conditions for restricting the right to privacy of communication in order to avoid unjustified violation of universally recognized fundamental human rights. The work discusses the issue of geolocating a person via their mobile phone, as well as legal regulation and judicial practice regarding the restriction of the right to privacy of communication in Europe and Russia. Anonymization as a necessary condition for processing personal data, including the privacy of communication, is also considered. The methodological basis of the study comprised dialectical, formal-legal, comparative methods, induction and analysis method. As a result, conclusions were drawn on the similarity of the legal regulation of the privacy of communication in Europe and Russia, on the possibility of restricting the right to privacy of communication at the legislative level, subject to the principles of proportionality, necessity and temporary nature of such restrictions caused by the pandemic, as well as on the legality of processing communication data (data on the location of users of communication services) on condition of anonymity, provided that it is impossible to deanonymize the data.